Student Graduation Prediction System In the MBKM Program Using The Mamdani Fuzzy Method - Muthiah Riani Harahap; Safwandi; Rini Meiyanti (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
This study aims to develop a graduation prediction system for the MBKM Program using the Fuzzy mamdani method. The system is designed to process various academic criteria such as GPA, internship experience, and other supporting documents to provide an accurate projection of graduation probability. The implementation was carried out using data from 61 students of the Informatics Engineering Department at Universitas Malikussaleh. The Fuzzy mamdani method was applied through stages of fuzzification, rule formation, fuzzy inference, and defuzzification to produce the final prediction. The test results show that this method is effective in handling uncertainty and provides a high prediction accuracy, where 67% of students were predicted to graduate, and 33% were not. This system can be used by academic staff to evaluate student performance and provide more precise guidance, as well as to help students plan their studies to achieve graduation in the MBKM Program.